Study on advances in the association between autoantibodies and clinical phenotypes in idiopathic inflammatory myopathy - ZHANG Hao, CHI Huihui, SU Yutong, YANG Chengde (Zhenduanxue lilun yu shijian, 2022)
Myositis specific autoantibodies(MSA) are important for the diagnosis and classification of idiopathic inflammatory myopathy (IIM). It reveales that there is a close relationship between various types of MSA and unique clinical manifestations as well as pathological phenotypes. The titers of some autoantibodies are also correlated with the disease activity score and prognosis. Therefore, detection of MSA is helpful to the identification of the disease subtypes, personalized treatment selection and the judgement of prognosis in clinical practice. In future, more in-depth researches on MSA are needed to furtherly explore the pathogenic mechanism of the disease.